Written communication in urban spaces: publication, textual materiality and appropriations - Gómez, Antonio Castillo (Ukrainian Cultural Studies, 2023)
The Routledge Companion to Cultural History in the Western World 1st editionEdited By A Arcangeli et al chapter Written communication in urban spaces: publication, textual materiality and appropriations pp. 310-331 by Antonio Castillo Gómez  © 2020 Routledge Reproduced by permission of Taylor & Francis GroupTranslated by Olena Pavlova
Keywords: cultural history; Written communication; publication; textual materiality; appropriation; urban spaces